A "turn-on" fluorescent probe based on V-shaped bis-coumarin for detection of hydrazine. Issue 7 (14th February 2020) - Jiang, Xingzong; Shangguan, Mingqin; Lu, Zhen; Yi, Sili; Zeng, Xiaoyang; Zhang, Yongle; Hou, Linxi
Abstract: Hydrazine (N2 H4 ) has been classified as an environmental contaminant and human carcinogen owing to its high toxicity. Exposed to high concentration of hydrazine can cause irreversible damage to human bodies. Hence, it is significant to explore an effective analytical method to selectively recognize and detect it. In this work, an intramolecular charge transfer (ICT) based probe 1 was designed and synthesized by condensation of V-shaped bis-coumarin and 4-bromobutyric acid. The V-shaped bis-coumarin with π-expanded system endowed the probe 1 larger stokes shift and superior tolerance to photobleaching. This "turn-on" probe exhibited a high selectivity towards hydrazine over other common ions and amine-containing species with a distinct fluorescent enhancement at 555 nm. It could rapidly detect hydrazine over a wide pH range and the detection limit was as low as 4.2 ppb. The large shift of absorption spectrum enabled it to detect hydrazine in real water samples and gas-state hydrazine by "naked-eyes". Graphical abstract: Image 1 Highlights: The novel V-shaped bis-coumarin with π-expanded system endowed the probe 1 larger stokes shift (95 nm) and superior tolerance to photobleaching. The large shift of absorption spectrum (103 nm) enabled it to detect hydrazine in real water samples and gas-state hydrazine by "naked-eyes". The probe 1 could detect hydrazine over a wide pH region (4-11) and low LOD value (4.2 ppb) within a short time (15 min).